Clinical Applications of MicroRNAs in Acute Myeloid Leukemia: A Mini-Review - Bhatnagar, Bhavana; Garzon, Ramiro (Frontiers in Oncology, 2021)
MicroRNAs (miRs) are short non-coding RNAs, typically 18-25 nucleotides in length, that are critically important, through their direct effects on target mRNAs, in a number of cellular processes including cell differentiation, proliferation and survival. Dysregulated miR expression has been identified in numerous cancer types including acute myeloid leukemia (AML). From a clinical standpoint, several miRs have been shown to associate with prognosis in AML patients. Furthermore, they also carry the potential to be used as biomarkers and to inform medical decision making. In addition, several preclinical studies have provided strong rationale to develop novel therapeutic strategies to target miRs in AML. This review will focus on potential clinical applications of miRs in adult AML and will discuss unique miR signatures in specific AML subtypes, their role in prognostication and response to therapy, as well as miRs that are promising therapeutic targets and ongoing clinical trials directed towards targeting clinically relevant miRs in AML that could allow for improvements in current treatment strategies.